Angular Projects - Second Edition - Bampakos, Aristeidis; Thompson, Mark (Packt Publishing, 2021)
Understand Angular web application development by building captivating real-world applications while exploring modern web technologies and best practices Key Features Explore Angular's capabilities for building applications across different platforms Combine popular web technologies with Angular such as monorepo, Jamstack, and PWA Build your own libraries and schematics using Angular CDK and Angular CLI Book Description Angular is a popular JavaScript framework that can run on a broad range of platforms including web, desktop, and mobile. It has an array of rich features right out of the box and a wide range of tools that makes it popular among developers. This updated second edition of Angular Projects will teach you how to build efficient and optimized web applications using Angular. You will start by exploring the essential features of the framework by creating ten different real-world web applications. Each application will demonstrate how to integrate Angular with a different library and tool. As you advance, you will understand how to implement popular technologies such as Angular Router, Scully, Electron, Angular service worker, Nx monorepo tools, NgRx, and more while building an issue tracking system, a PWA weather application, a mobile photo geotagging application, a component UI library, and many other exciting projects. Toward the concluding chapters, you'll get to grips with customizing Angular CLI commands using schematics. By the end of this book, you will have the skills you need to be able to build Angular apps using a variety of different technologies according to your or your client's needs. What you will learn Set up Angular applications using Angular CLI and Nx Console Create a personal blog with Jamstack and SPA techniques Build desktop applications with Angular and Electron Enhance user experience (UX) in offline mode with PWA techniques Make web pages SEO-friendly with server-side rendering Create a monorepo application using Nx tools and NgRx for state management Focus on mobile application development using Ionic Develop custom schematics by extending Angular CLI Who this book is for If you are a developer who has beginner-level experience with Angular and are looking to become well-versed with essential tools and deal with the various use cases you may encounter with Angular, then this Angular development book is for you. Beginner-level knowledge of web application development and basic experience working with ES6 or ...